HCL: Distributing Parallel Data Structures in Extreme Scales - Devarajan, Hariharan; Kougkas, Anthony; Bateman, Keith; Sun, Xian-He (Proceedings / IEEE International Conference on Cluster Computing, 2020)
Most parallel programs use irregular control flow and data structures, which are perfect for one-sided communication paradigms such as MPI or PGAS programming languages. However, these environments lack the presence of efficient function-based application libraries that can utilize popular communication fabrics such as TCP, Infinity Band (IB), and RDMA over Converged Ethernet (RoCE). Additionally, there is a lack of high-performance data structure interfaces. We present Hermes Container Library (HCL), a high-performance distributed data structures library that offers high-level abstractions including hash-maps, sets, and queues. HCL uses a RPC over RDMA technology that implements a novel procedural programming paradigm. In this paper, we argue a RPC over RDMA technology can serve as a high-performance, flexible, and co-ordination free backend for implementing complex data structures. Evaluation results from testing real workloads shows that HCL programs are 2x to 12x faster compared to BCL, a state-of-the-art distributed data structure library.